Exploring Leadership Effectiveness and Its Impact on Performance: A Systematic Literature Review - Apriansyah, Angga; Ardyanti, Aprilia; Djastuti, Indi; Hidayati, Retno (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2024)
An efficient human resources department plays a pivotal role in propelling a company’s growth trajectory. Acknowledging that human resources represent the company’s greatest asset, the impact of their performance on overall results and profits cannot be overstated. This study undertakes a comprehensive review of leadership effectiveness through the literature review method, employing the PRISMA method to identify and analyze 53 articles on various aspects of leadership effectiveness. The findings underscore the critical role of effective leadership in modern business, emphasizing its influence on how teams achieve goals by adeptly adapting to cultural and circumstantial nuances. Successful leadership is portrayed as a multifaceted approach involving guidance, strategic thinking, and inspiration. The study recognizes the dynamic interplay between leadership, organizational context, and diversity, stressing the need for leaders to adapt to economic fluctuations, industry dynamics, and evolving communication landscapes. Furthermore, leadership emerges as a catalyst for heightened employee engagement, morale, and productivity, fostering an environment conducive to innovation. The study underscores the necessity for leaders to navigate cultural norms in diverse regions, highlighting the importance of understanding and adapting to the unique cultural fabric of their teams within this dynamic domain.